An Economic Analysis of impact of the exchange rate on agricultural trade balance in Iraq for the period 2003-2022 (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:            The study aims to identify impact of the exchange rate on the size of the agricultural trade balance gap, and study impact in the short and long relationship between variables in Iraq for the period 2003-2022.The study used the econometric approach to analysis using the modern methodology of co-integration, and found a relationship between the exchange rate and the agricultural trade balance gap, it appeared in a positive relationship in the short term and an inverse relationship in the long term., Adopting an exchange rate policy contributes to increasing foreign trade and the need to pay attention to diversify sources foreign trade and export in Iraq.